An assessment of the effect of green innovation, income, and energy use on consumption-based CO2 emissions: Empirical evidence from emerging nations BRICS. (10th September 2022) - Jiang, Qingquan; Rahman, Zia Ur; Zhang, Xiaosan; Islam, Md Saiful
Abstract: Energy and green innovation are important to a country's economic progress, but the externalities of increased pollution as a result of a rise in energy used and economic growth must not be overlooked. Within the Stochastic Impacts by Regression on Population, Affluence, and Technology (STIRPAT) framework, this study aims to check empirically the effect of environment-related technologies (ERT), coal consumption (CC), economic growth (EG), and population density (PD) on the consumption-based CO2 emissions (CCO2e ) in the BRICS (i.e., Brazil, Russia, India, China, & South Africa), as with fast economic progress BRICS is facing problems of CO2 emission. The econometric techniques of the cross-sectional dependence test, slope heterogeneity test, and second-generation panel unit root test were used to check the nature of the data. The available balance data over the period 1985–2018 were analyzed via Driscoll and Kraay and a dynamic common correlated effect mean group (DCCEMG). Long-term empirical findings show that ERT has a negative impact on the CCO2e, while per capita GDP and CC have a positive impact on CCO2e . Empirical evidence recommends that ERT is important for BRICS countries' long-term sustainability. It is suggested that policymakers should encourage ERT that help in curbing their CO2 emanations.